Analisis Hubungan Usia, Masa kerja dan Pengetahuan terhadap Keluhan Musculoskeletal Disorders (MSDs) - Indriyani, Indriyani; Badri, Putri Rizki Amalia; Oktariza, Rury Tiara; Ramadhani, Ria Salsabila (Jurnal Kesehatan, 2022)
Workers are human resources who have a very influential and significant role in carrying out the production process, especially manual activities. The production process in a workplace still requires manual human handling in the process of work, but humans have abilities and limitations both physically and non-physically that are often related to musculoskeletal. The health problem that occupies the first position associated with the job is Musculoskeletal Disorders. Method: The design of the study used in this study is to use a cross-sectional approach. Result: Data in analysis with statistical tests using chi-square test. showed the result of p-value=0.035 for age relationships and Musculoskeletal Disorders (MSDs) complaints); p-value= 0.013for working period relationship Of Work Ergonomics Knowledge Against Complaints; p-value=0.000 for working period relationship of Work Ergonomics Knowledge Against Complaints. Conclusion: Research conducted on freelance daily workers of Palembang Public Works and Spatial Planning Office shows that there is a relationship between age, working period, and ergonomic knowledge of Musculoskeletal Disorders (MSDs) complaints.Â